Times have Changed – Is it Time to Consider Restructuring the CAG? - William G Paterson (Canadian Journal of Gastroenterology)
Following the 2005 annual general meeting of the Canadian Association of Gastroenterology (CAG) where certain proposals for CAG bylaw revisions were tabled, the CAG Board decided to create an ad hoc committee to take a more comprehensive look at restructuring the CAG management, which in turn would result in proposals for bylaw amendments. A committee consisting of William Paterson, Des Leddin, Ronald Bridges, Mary Perdue, John Wallace and Paul Sinclair was formed. This committee endorsed the need to make fundamental changes in the structure of the CAG management to streamline the operations of the organization and better achieve its strategic goals. It was further agreed that the process for implementing change must involve broad consultation with the CAG Board and the membership. The present document represents the first step in this consultative process.